2004
DOI: 10.1081/pln-120030376
|View full text |Cite
|
Sign up to set email alerts
|

Flower and Foliar Analysis for Prognosis of Sweet Cherry Nutrition: Influence of Different Rootstocks

Abstract: This research was aimed to study the interest of flower analysis as a tool for the prognosis of nutritional deficiencies on cherry trees and confirm the influence of rootstock on the mineral uptake by tree. This type of diagnosis is compared with foliar analysis. The trial was In general, the P. cerasus rootstocks (CAB 6P, CAB 11E and MM 9) showed values of leaf mineral elements more adequate, and also higher values of leaf chlorophyll concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 14 publications
10
37
0
Order By: Relevance
“…Additionally, apart from rootstock, species and/ or genotypes play a key role in determining the Na content in the flowers of fruit crops, which is in agreement with previous work in flower (ZARROUK et al, 2005). The average content of Na in plum organs suggested the following trends: 1-year old shoots > 2-year-old shoots > flower buds > flower (JIMÉNEZ et al, 2004).…”
Section: Content Of Sodium (% Of Dry Weight)supporting
confidence: 79%
See 2 more Smart Citations
“…Additionally, apart from rootstock, species and/ or genotypes play a key role in determining the Na content in the flowers of fruit crops, which is in agreement with previous work in flower (ZARROUK et al, 2005). The average content of Na in plum organs suggested the following trends: 1-year old shoots > 2-year-old shoots > flower buds > flower (JIMÉNEZ et al, 2004).…”
Section: Content Of Sodium (% Of Dry Weight)supporting
confidence: 79%
“…In addition, Zarrouk et al (2005) indicated that only flower Zn concentration in peach was significantly correlated with Zn in leaves, as opposed to the other nonsignificant correlations. Similar data were reported by Sanz and Montañés (1995) for peach and Betrán et al (1997) and Jiménez et al (2004) for cherry. A PCA, one of the multivariate statistical procedures, was used to establish relationships among shoots, flower buds and flowers and to study correlations regarding Na content within sets of rootstock/cultivar combination.…”
Section: Evaluation Of Correlations Among Variables and Principal Comsupporting
confidence: 77%
See 1 more Smart Citation
“…The amount of this element in the leaves of the studied cultivar was lower than that reported in the literature for the 'Bing' and 'Sunburst' cultivars [Neilsen andKappel, 1996, Jiménez et al 2004]. Zinc content in the leaves was similar to the levels in 'Bing' cultivar [Neilsen and Kappel 1996], and copper content was comparable to the amount of copper accumulated by the leaves of 'Sunburst' cultivar [Jiménez et al 2004]. In our experiment, the content of cadmium in the leaves and fruits was decreased following the fertilization ( …”
Section: Resultsmentioning
confidence: 61%
“…They have been used as an indicator of iron chlorosis tolerance in different Prunus trees (Jiménez et al, 2004(Jiménez et al, , 2008El-Jendoubi et al, 2012). Based on these results, GF 655/2 and Monpol appear to be more sensitive to iron deficiency in compact and calcareous soils.…”
Section: Leaf Chlorophyll Concentrationmentioning
confidence: 95%